A justiça distributiva como critério fundamental nas políticas públicas: o caso dos jogos panamericanos na cidade do Rio de Janeiro - Silva, Carlos Henrique Dantas da (2005)
This dissertation is a project of evaluation of the proposals of the Panamerican Games of 2007, that they will be carried through in the city of Rio De Janeiro. Great events present the possibility of improvement of the urban space and economic development, amongst other chances seen by politics and urban planners well. For this work we search to argue the city as field of specific study, understanding it in the current world-wide scene of globalization and computerization, the relations politics, economic and social existing interns. We search in material literature to study and to evaluate what it would be a ¿good city¿ and studies that had understood the development of the urban space. We also look for to understand the city of Rio de Janeiro as a singular urban space, since the origin of the city as a urban space, passing for the proposals gifts of modification of the carioca space. We dedicate part of the work, inside of the chapter where we understand the city of Rio de Janeiro, the presentation of the project of the Panamerican of 2007, comparing it with great previous events. The vision of technique and politics during the interviews was essential for the best understanding of the proposals of the Games. Finally we evaluate the proposals of modification of the Pan2007 for the city of Rio de Janeiro with the methodology of Kevin Lynch to evaluate the good form of the city' in communion with the proposal of distributive justice of Rawls. The result of this evaluation was that the current proposals of modification of the city for the Pan2007 will be able to generate resulted not deliberate for a considerable parcel of the population and to modify the economic relations harmfully, social and politics inside of the territory of the city. For such we consider measured compensatory satisfactory that they can reach the objectives of an equal citizenship and an equitable equality of chances, starting for the offering of the social minimums of just form. '